An Austrian Take on ESG - Schneider, Henrique (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
This paper analyzes the contemporary debate about ESG – Environment, Social, Governance – using economic insights from Austrian Economics; particularly, on entrepreneurship, agency, and information asymmetry. These insights are contrasted to similar concepts in “mainstream” economics suggesting that the Austrian insight goes beyond them, first by stressing effectiveness in addition to efficiency and institutions in addition to law-likeliness. When applied to ESG, the Austrian insight portraits ESG as a special case of the socialist, or economic calculation debate causing misalignments between inter- and intrafirm goals, exacerbates agency problems and suffers from serious flaws in its conceptualization as well as methodology. Relying on entrepreneurship, however, could make ESG work. This paper, thus, applies Austrian economics to contemporary debates claiming that its insights provide a unique perspective but at the same time updating its research program.